Epworth League Institute at Russian River - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the Epworth League Conference at Russian River. Some attendees hold banners indicating a region of origin or organization they identify with, these include the following: "Windsor," "Mayfield," "San Jose," "North Sacramento," and "Shattuck."